EFEKTIFITAS METODE CERAMAH DALAM PENYAMPAIAN DAKWAH ISLAM: Studi pada Kelompok Pengajian di Perumahan Mojosongo Permai Kabupaten Boyolali - Maryatin, Maryatin (Da'wa and Communication Faculty State Islamic University Walisongo, Semarang, Indonesia, 2014)
This is a qualitative research that generates two discriptive forms namely people’s written or spoken and also the behavior that can be observed. Through the qualitative approach which emphasised on the usage of observational techniques involved (participant observation) and in-depth interviews (indepth-interview) in date collection. Participant observation techniques used to obtain a detailed picture of the society condition in the residential neighbourhood of Mojosongo Permai. The results of this research showed that the implementation of payroll in the Mojosongo Permai residential neighborhood that generally has two substantial investigations, investigations of women called